Analisis perbandingan rencana strategi pada Bank digital Syariah di Indonesia - Fitriani, Ika Lutfia; Zahro, Amelia; Ummi, Laely Sa’idatul (Maliki Interdisciplinary Journal, 2024)
A strategic plan is one of the key components in managing a sharia digital bank to achieve long-term success. This research aims to analyze the strategic plans of three leading sharia digital banks: Bank Aladin Syariah, Bank Victoria Syariah, and Bank Mega Syariah. In this research, we identified key elements in each bank's strategic plan, including vision, mission, strategic goals, and tactical steps taken to achieve those goals. The analysis results show that the three sharia digital banks have a strong vision and mission to provide innovative and inclusive sharia financial services. They also have strategic objectives that are in line with sharia principles, such as sustainable profitability and community empowerment. Additionally, these three banks are taking tactical steps that include developing digital products and services, investing in information technology, and thoughtful marketing efforts. However, there are differences in the strategic approaches of these three banks. Bank Aladin Syariah focuses more on market expansion through partnerships with small and medium businesses. Bank Victoria Syariah emphasizes customer empowerment through a high technology-based approach. Meanwhile, Bank Mega Syariah combines a partnership strategy with innovative product development. Thus, this research provides insight into the various strategic plans adopted by leading Islamic digital banks. This analysis can become the basis for these banks to improve their strategies, face the challenges of the evolving market, and provide better Islamic financial services to their customers.